Global Trends in Research on Biological Control Agents of Drosophila suzukii: A Systematic Review - Lenon Morales Abeijon; Júlia Birkhan; Jana C. Lee; Sérgio Marcelo Ovruski; Flávio Roberto Mello Garcia (Insects)
It is essential to consolidate knowledge on biological control agents (BCAs) for Drosophila suzukii, to identify gaps, evaluate the effectiveness of existing strategies, and guide future research toward sustainable pest management. The biological control of SWD has been explored through various BCAs, focusing on parasitoids, predators, and entomopathogens. We conducted a systematic review using Web of Science and Scopus (2012–2023) to investigate global research on BCAs of SWD. Our goal was to synthesize and categorize the current scientific production, addressing questions such as (1) publication numbers per BCA group and species, (2) key BCAs, (3) common methodologies (laboratory, field, greenhouse, or combined), (4) research scope, (5) effectiveness of BCAs, and (6) countries conducting research. We found 585 records, 184 of which were suitable for analysis. The most studied BCAs are parasitoids, comprising 64% of publications, with Trichopria drosophilae and Pachycrepoideus vindemmiae being the most researched, followed by Leptopilina japonica and Ganaspis kimorum. Entomopathogens and predators represent 26% and 7% of publications, respectively. Studies under controlled conditions predominate, and surveys, identifications, and characterization of natural enemies are the main research foci, followed by conservation biological control showing the highest effectiveness.